Memory and Non-Place: Visual Testimonies of Japanese American Internment During World War II. Issue 1 (2nd January 2019) - Lee, Ana Paulina
Abstract : This article addresses the little-known history of Japanese Latin American internment during WWII. Classified as 'illegal aliens' and 'enemy aliens', 2, 264 Japanese Latin Americans were stripped of citizenship from their home countries, denied rights in the United States, and ultimately deprived reconciliation due to their undocumented status. Using the traces of this history as a case study, I explore the strategic memories Japanese Latin Americans create about non-place – spaces of statelessness or states of exception – that allow them to make claims about state violence committed against them under these conditions, and, second, argue that demands for justice against political violence entail not only bringing light to erased histories but also developing engaged acts of reception that account for survivors' claims to the memories of non-place. Visual testimonies, such as the Denshō Digital Archive and the short documentary Hidden Internment: The Art Shibayama Story (2004), affectively connect a viewer/listener to the memory of trauma, to an inexpressible haunting, and thus are critical platforms for creating a collective memory between survivors and the digital generation of postmemory.